The problems with trade secret protection/overprotection in Asia - LIU, Kung-chung (Institutional Knowledge at Singapore Management University, 2022)
Trade secret protection law has been an important complement to patent law and has gained increasing importance over the last three decades, not least in Asia. Major Asian countries are now at a crossroads, as some (Japan, Korea, Thailand, Taiwan, and China) are following the US approach to criminalizing trade secret infringement and imposing harsher penalties on economic espionage (Japan, Korea, Taiwan, and China). This paper identifies many of the problems associated with trade secret protection, provides indicators of the overprotection of trade secrets, and warns against its many side effects. It then points out the crossroads that Asian economies are now at and provides some suggestions for Asian jurisdictions to consider: basing trade secret protection on commercial realities, working trade secret protection in tandem with the patent regime, and learning from the German model of moderate criminal punishment for trade secret infringement and protecting employee mobility by limiting non-competition clauses.